Pengaruh variasi temperatur tempering terhadap sifat mekanik dan struktur mikro baja aisi 1045 - Muhammad Riadi Barsuma Jaya; Harnowo Supriadi; Muhammad Badaruddin; Shirley Savetlana; Irza Sukmana (Fakultas Teknik Universitas Lampung, 2022)
This study aims to determine the effect of variations in tempering temperature on the strength properties of steel by knowing the value of the tensile test and changes in the microstructure of the steel. This study uses AISI 1045 steel formed using the ASTM-E8 standard with a cylindrical shape. Then the steel is given quenching heat treatment at a temperature of 850°C with a holding time of 90 minutes, then after being given quenching heat treatment with water cooling media then the reheating process is also called the tempering process with temperature variations of 450°C, 550°C and .650 °C then after that the holding time for 60 minutes. After the entire heat treatment process has been completed, then the tensile test and microstructure observations are also called OM. In this study, the ultimate stress value of 693.7 MPa and yield strength of 391.2 Code R1 (450°C) and temperature of 450°C had the ultimate stress of 1066.8 MPa and yield strength of 995.7 MPa. Code R2 (650°C) at a temperature of 650°C has an ultimate stress of 733.3 MPa and a yield strength of 647.4 MPa. Code R3 (550°) tempering temperature of 550°C has an ultimate stress of 862.8 MPa and a yield strength of 778.9.